Potential critical risks of pulmonary thromboembolism from an asymptomatic postpartum ovarian vein thrombosis: a case report - Tsuyoshi Murata; Yuki Yoshimoto; Yoshiaki Shibano; Koji Owada; Masayuki Miyajima; Soichi Nakamura; Ryuji Yamauchi (BMC, 2022)
Abstract Background Ovarian vein thrombosis (OVT) may cause maternal mortality by inducing pulmonary thromboembolism (PTE). However, the prevalence, etiology, risk factors, prognosis, and optimal treatments for asymptomatic OVT during and after pregnancies are unclear, which therefore requires a high clinical index of suspicion for certain diagnoses due to its vague presentation. We herein present a case of asymptomatic postpartum OVT that extended toward the inferior vena cava (IVC), resulting in a potential risk of PTE. Case presentation A 30-year-old postpartum woman presented with slight dyspnea after an uneventful vaginal delivery at 40 weeks of gestation. We checked her laboratory data to exclude lethal thrombosis; D-dimer levels were 85.6 μg/mL. We performed computed tomography (CT) to search the presence of PTE and deep vein thrombosis (DVT); although no signs of PTE and DVT in her legs were detected, CT and trans-abdominal ultrasonography (TAUS) revealed a right OVT. Heparin was administered, and D-dimer levels decreased; warfarin at a dose of 2 mg/day was subsequently administered to control anti-coagulopathy. However, D-dimer was re-elevated despite adequate anticoagulation treatment, and extension of the right OVT to the IVC was detected by CT and TAUS. With warfarin administration, CT and TAUS showed the disappearance of right OVT. The patient was discharged from the hospital 17 days after delivery. Conclusions Even asymptomatic postpartum OVT may lead to PTE. Universal screening guidelines and optimal treatment strategies for asymptomatic OVT in pregnant and postpartum women should be established through future studies.